ENVIRONMENTAL AND SAFETY ATTRIBUTES GEOSTRATEGIC HEGEMONY - A. Bohan (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2014)
The article deals with modern aspects of manifestation geostrategic hegemony in the context of its environmental and safety attributes that determine the appearance of new determinants of economic development and progress of the world. Specificity of the geopolitical sphere in the context of a retrospective and prospects of development of civilization, which requires the use of new system-methodological approaches to its study. Defined mechanisms to enhance the status of the hegemon, which by their nature are accompanied by threats and challenges of globalization and conflict-military factors in the fight for resources and ecological imbalance in the world. The space competition geopolitical actors are increasingly extended to third countries, thus causing their economic instability, environmental vulnerability and permanent conflict. The factors, causes and conditions for the identification of new measurements geostrategic hegemony, which can affect the configuration of world order, the balance of economic power and the establishment of constructive international dialogue aimed at security, sustainable development and well-being of all mankind.